Role of principal in promoting teachers unity: evaluation in Malaysian secondary schools - Alias, Bity Salwana; Nor Zainuddin, Zaida; Ishak, Mohd Radzi; Mansor, Azlin Norhaini (Universiti Pertanian Malaysia Press, 2021)
The inability of teachers to accept cultural, linguistic, and religious differences caused by racial differences can have a negative impact on unity. The literature suggests that principals can play a role in addressing this issue. Thus, the purpose of this study is to determine the principal’s role in promoting teachers’ unity and to determine the relationship between the principal’s role and teachers’ unity. This study is a survey design and a quantitative method was used to collect data from 578 teachers in a population of 236,748 teachers in secondary school. The data collected was analyzed descriptively to produce mean value and standard deviation, therefore the level of principals’ role in promoting unity and the level of teachers’ unity can be interpreted. Inference analysis by Pearson correlation was done to determine r-value, therefore the hypotheses on the relationship between the two variables were tested. Overall, principals’ role attained a high level in promoting unity with a mean score of 3.85, whereas the teachers’ unity level was also at a high level with a mean score of 4.37. The result also shows that there was a positive relationship between the two variables but at a weak level with r = 0.20. This paper contributes to the body of knowledge that principals’ role in promoting unity has had an impact on the teachers’ unity level. This finding also shows that the Malaysian Education System Aspiration focusing on promoting unity is relevant and should be continuously implemented. Apart from having theories implication, the findings bear positive input for principals’ training, and also provide input for the teaching fraternity to be more respectful towards each other’s differences, thereby avoiding racism and discrimination amongst them.